Outcomes of patients with self-posioning with organophosphorous pesticides at a rural tertiary care hospital in Southern India - Falia, Mitesh D.; Kulkarni, Prasad; Reddy, Narsimha; P., Somashekaram (International Journal of Research in Medical Sciences, 2017)
Background:Organophosphate (OP) pesticides are the main agents for pest control in agricultural crops making them the agent of choice for self-poisoning. In India, self-poisoning with OP pesticides is the second most frequently reported method of suicide owing to its ready and easy availability with mortality varying from 12% to 50%. Methods: A retrospective study was conducted over a period of one year to compare the socio-demographic variables with the outcomes in patients with OP poisoning. A total 94 patients were consecutively included in the study and a statistical analysis was carried out. Results: Majority of the patients belonged to the 21-30 years age group (54.3%), emphasizing the involvement of the young and productive age group into suicidal attempts. The study population consisted of 58 males (61.7 %) and 36 females (38.3%) depicting a higher incidence of OP poisoning amongst males. There was an overall mortality of 3.2 % amongst the treated patients. Females had a higher mortality (5.6%) as compared to males (1.7%). It was observed that the mortality was the maximum among the 41-50 years age group patients (p = 0.007). Conclusions: Self-poisoning with OP pesticides is highly prevalent in the rural areas due to the ease of availability of these compounds and lack of regulatory control over the same. The young population is the most commonly affected by this. Regulation in sales and distribution of pesticides should be taken as a priority and early treatment yields a favourable outcome in majority of the patients.